Determinan Pengeluaran Konsumsi Pangan Rumah Tangga Miskin di Kabupaten Solok - Mita Oktavia; Sri Ulfa Sentosa (Universitas Negeri Padang, 2026)
This study aims to analyze the socioeconomic factors that influence food consumption expenditures among poor households in Solok Regency and to examine the simultaneous relationship between food consumption expenditures and household income. This study employs a quantitative approach using secondary data from the 2024 National Socioeconomic Survey (SUSENAS). The variables used include income, marital status, age of the head of household, education level of the head of household, and internet access. The sample consists of 10,354 poor households in the bottom 40 percent of expenditure (deciles 1 through 4) in Solok Regency. The data were analyzed using the Two-Stage Least Squares (2SLS) method. The results of the study show that: 1) Income, marital status, age of the head of household, education level of the head of household, and internet access have a significant effect on food consumption expenditures among poor households. 2) Food consumption expenditure, the age of the head of household, the head of household’s education level, and internet access have a significant effect on the income of poor households, whereas marital status does not have a significant effect. This study indicates a simultaneous relationship between food consumption expenditures and the income of poor households. The findings are expected to provide input for local governments in formulating policies to improve the welfare and food security of poor households in Solok Regency.